Activity of mannitol and hypertonic saline therapy on the oxidant and antioxidant system during the acute term after traumatic brain injury in the rats - Yilmaz, Nebi; Dulger, Haluk; Kiymaz, Nejmi; Yilmaz, Cahide; Gudu, Burhan O.; Demir, Ismail (Brain research, 2007)
In this study, our objective is to investigate the effects of mannitol and 7.5% hypertonic saline (HS) therapy on the levels of malondialdehyde (MDA), catalase and glutathione peroxidase (GSH-Px) in the early stages of experimental head traumas in rats. Rats included in the study were divided into four groups: Group I Control, Group II Trauma, Group III Mannitol, and Group IV 7.5% Hypertonic Saline. Rats in Group II were subject to head trauma only. Mannitol was injected intraperitoneally to rats in Group III after head trauma and 7.5% HS was injected intraperitoneally to rats in Group IV after head trauma. Rats were sacrificed 4 h after administration of mannitol or 7.5% HS, and the levels of MDA catalase and GSH-Px in brain tissues extracted from rats were determined. MDA levels in the trauma group were significantly increased compared with the control group ( p < 0.01), whereas there was a reduction in catalase and GSH-Px levels, although these differences were not significant. By contrast, in the mannitol group, MDA, catalase and GSH-Px levels were lower than the levels in the trauma group, and these reductions were statistically significant ( p < 0.05). The MDA, catalase and GSH-Px levels of the 7.5% HS group were lower than those of the trauma group; however, this reduction was not statistically significant. It was concluded that mannitol and 7.5% HS therapies that are used to reduce intracranial pressure and to increase the use of catalase, an antioxidant enzyme, and GSH-Px, are likely to reduce cellular damage by reducing the formation of MDA, the levels of which are known to be indicative of cellular level oxidant damage.